Prediction of Osteoporosis through Radiographic Assessment of Proximal Femoral Morphology and Texture in Elderly; is it Valid and Reliable - Özkan Köse; Ömer Faruk Kılıçaslan; Hasan Onur Arık; Ümit Sarp; İclal Erdem Toslak; Mehmet Uçar (Galenos Yayinevi, 2015)
Objective: The purpose of this study was to determine the best predictive radiographic measurement method to identify the presence of osteoporosis and test the inter-observer and intra-observer reliability and validity of these methods in postmenopausal women. Materials and Methods: Ninety-two elderly female patients who presented with hip pain were included. Hip radiographs were used to determine the values of Singh index (SI), canal-to-calcar ratio (CCR), and cortical thickness index (CTI). All measurements were performed by two independent observers on two separate occasions, at least 4 weeks apart. Bone mineral density (BMD) was assessed by DEXA. In the first part of the analysis, reliability of the all measurement methods was tested. In the second part, correlation coefficient (Pearson r) was used to determine the relationship between the measurement methods and BMD. Finally ROC curve analysis was performed to determine the sensitivity, specificity, and threshold values for each radiographic measurement method. Results: Intra-observer reliability analysis of SI revealed kappa coefficient of 0.359 for observer A, and 0.224 for observer B. Inter-observer reliability analysis of SI revealed kappa coefficient of 0.070 for observer A and 0.051 for observer B. The intra-observer and inter-observer reliability was good and excellent for CTI and CCR for both observers (ICC: 0.920 and ICC: 0.936). There was no correlation between SI and BMD (p=0.818). On the other hand, there was a significant correlation between CTI and CCR and BMD (p=0.001). All measured indices were significantly different (p<0.05) between osteoporotic and non-osteoporotic patients. CTI value less than 0.3 or CCR value less than 0.47 reflects the presence of osteoporosis with 100% sensitivity and 98% specificity. Conclusion: SI is not reliable and do not correlate with BMD. However, both CTI and CCR showed good and excellent reliability, and each index correlated well with the real BMD values. (Türk Osteoporoz Dergisi 2015;21: 46-52)